Rumble in the Jungle: The J. Lawton Collins Mission to Vietnam and the Regime that Nearly Crumbled - Jackson, Alex (Kansas State University. Dept. of History, 2013)
Many are familiar with the political fallout associated with American military involvement in Vietnam. However, there are aspects of the early American presence that have received scant attention by historians. One such incident is that of the J. Lawton Collins Mission to Vietnam, which now serves as a watershed moment in history. The United States supported the South Vietnam-based Republic of Vietnam, led by Ngo Dinh Diem. The Eisenhower administration sought to shore up the sovereignty of the Diem government by sending Collins as a special advisor. Collins subsequently came of the opinion that Diem was unsuited to lead the country and that United States interests would be better served with somebody else holding the reigns of government. Collins’s opinion stemmed from an anti-communist domino effect ideology, meaning that the South Vietnamese must be united under a strong leader to combat the invasion of communism. Ultimately, the United States government does not act upon Collins’s recommendations and the mission ends. Through analysis of the secondary research conducted on the period as well as utilizing lecture notes and primary sources such as Collins’s memoir, this paper finds that at the point of the Collins Mission, two roads presented themselves to the U.S. government: force the unpopular and inexperienced Diem out of power, or allow the facade he presented to stand. This paper concludes that this was a true watershed moment in the history of the Vietnam conflict, and ultimately calls for the recognition that history is a narrative and that those points where historical actors decided to choose one option over another have had lasting effects on the course of human events.
Keywords: J. Lawton Collins; Eisenhower; Diem; Cold War; Vietnam